A photovoice study on the perceptions among unemployed youth of information technology in Mamelodi, South Africa - Magogodi Nkuna; Martina Jordaan; Peter Zängl (Social Work & Society, 2020)
Photovoice is a method of qualitative social research. It has potential to analyze living environments, social spaces and organisations. In the following, we describe the theoretical framework of Photovoice in the context of the approach of lifeworld orientation. We then will be showing the benefit of the method using a study on perceptions of information technology among unemployed youth and their connections in Mamelodi, South Africa. This example points out that photovoice is an effective method to give vulnerable people a voice to tell a story about their lives and their community. This can play an important role in the profession of social work in the context of the analysis of the lifeworlds of its addressees.